How Hospice Saved My Mother's Life - Ann Green (Patient Safety, 2020)
How are you doing with all of this?” asked the hospice social worker. We sat in a small recreation room in the skilled nursing facility. I had just signed the paperwork to put my 81-year-old mother on hospice. I didn’t know how to answer the question. In the last three months, my father had passed away, my mother had fallen and broken a hip, and then fallen again in rehab and broken her other hip. Post hip repairs, instead of recovering, Mom had almost stopped eating; had a hard-to-shake urinary tract infection; developed a pneumonia that needed IV [intravenous] antibiotics; and, worst of all, had a rapid cognitive decline.